Constitutional Activism and Democratic Consolidation: The Role of the Constitutional Court of Kosovo - Selimi, Behar; Jashari, Murat (PRAWO i WIĘŹ, 2026)
This paper examines the evolving role of the Constitutional Court of Kosovo in shaping democratic governance through constitutional adjudication. Focusing on its jurisprudence on presidential elections and government formation, it analyses how constitutional procedures, voting thresholds, and institutional mandates have been interpreted in a fragile post-conflict context. This paper argues that the Court has played a decisive role in resolving political impasses by clarifying constitutional ambiguities and enforcing procedural discipline where political institutions have failed to act. Drawing on theories of judicial activism and procedural constitutionalism, this paper contends that the Court has functioned as a stabilising force in Kosovo’s constitutional order. While some decisions reflect a strict formalist approach, others demonstrate adaptive reasoning aimed at safeguarding democratic continuity and constitutional legitimacy. It concludes that constitutional activism has contributed to democratic consolidation, though its long-term sustainability depends on a balanced relationship between judicial authority, political responsibility, and constitutional reform.